Decolonial ethnomathematics and the ethnographic education of Mathematics teachers - Dias, Douglas Matheus Gavioli (Educação Matemática Debate, 2025)
The study is justified by offering guidelines that help teachers understand the cultural and social challenges and demands of students, integrating them into the teaching of Mathematics. To this end, a theoretical foundation was developed based on Ethnomathematics, teacher education, Decoloniality and decolonial Ethnomathematics, to develop concepts that lead to on-demand ethnography as a possibility of affective/methodological education of Mathematics teachers through decolonial Ethnomathematics. The study, of a theoretical nature, is configured as an essay. In the end, three aspects for the affective/methodological education of teachers were identified: i) allowing oneself to be affected through a sentipensante attitude; ii) knowing the environment inserted by the precepts of on-demand ethnography and liberating pedagogy; iii) decoding of signs based on emic ethnomodeling.